Effects of 1-methyl-1, 2, 3, 4-tetrahydroisoquinoline on a diabetic neuropathic pain model - Tokhi, Ahmed; Ahmed, Zainab; Arif, Mehreen; Rehman, Naeem Ur; Sheibani, Vahid; Sewell, Robert D. E.; Rauf, Khalid (Frontiers in Pharmacology, 2023)
Abstract: Background: Neuropathy is a prevalent and debilitating complication of poorly managed diabetes, contributing towards poor quality of life, amputation risk, and increased mortality. The available therapies for diabetic neuropathic pain (DPN) have limitations in terms of efficacy, tolerability and patient compliance. Dysfunction in the peripheral and central monoaminergic system has been evidenced in various types of neuropathic and acute pain. The objective of the present study was to investigate 1-methyl 1, 2, 3, 4-tetrahydroisoquinoline (1MeTIQ), an endogenous amine found in human brain with a known neuroprotective profile, in a model of streptozotocin (STZ) induced neuropathic pain. Methods: Diabetic neuropathy in male BALB/c mice was induced by intraperitoneal injection of a single dose of STZ (200 mg/kg). Upon development of DPN after 4 weeks, mice were investigated for mechanical allodynia (von Frey filament pressure test) and thermal hyperalgesia (tail immersion test). Ondansetron (1.0 mg/kg i.p.), naloxone (3.0 mg/kg i.p.) and yohimbine (2.0 mg/kg i.p.) were used to elucidate the possible mechanism involved. Postmortem frontal cortical, striatal and hippocampal tissues were dissected and evaluated for changes in levels of dopamine, noradrenaline and serotonin using High-Performance Liquid Chromatography (HPLC) with UV detection. Results: Acute administration of 1MeTIQ (15-45 mg/kg i.p.) reversed streptozotocin-induced diabetic neuropathic static mechanical allodynia (von Frey filament pressure test) and thermal hyperalgesia (tail immersion test), these outcomes being comparable to standard gabapentin. Furthermore, HPLC analysis revealed that STZ-diabetic mice expressed lower concentrations of serotonin in all three brain regions examined, while dopamine was diminished in the striatum and 1MeTIQ reversed all these neurotransmitter modifications. These findings suggest that the antihyperalgesic/antiallodynic activity of 1MeTIQ may be mediated in part via supraspinal opioidergic and monoaminergic modulation since they were naloxone, yohimbine and ondansetron reversible. Conclusion: It was also concluded that acute treatment with 1MeTIQ ameliorated STZ-induced mechanical allodynia and thermal hyperalgesia and restored brain regionally altered serotonin and dopamine concentrations which signify a potential for 1MeTIQ in the management of DPN.